Role of leadership in nurturing shared values supportive of innovation culture - 359495 Abdulmajid Al-Jilani Al-Mishri Rahuma; Wan Khairuzzaman Wan Ismail, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Ph.D (Pengurusan Teknologi)) - Universiti Teknologi Malaysia, 2008